A Change in Perspective: Agriculturally -Based Study Abroad Experience for Nicaraguan Students - Mark S. Hainline; Baleshka Brenes Mayorga; Sarahi Morales; Amy E. Boren Alpízar; Rudy A. Ritz; Scott Burris (Journal of International Agricultural and Extension Education, 2018)
Study abroad experiences serve to enrich students’ educational experiences, granted these programs must be evaluated to assess educational effectiveness. The purpose of this qualitative study was toexamine Nicaraguan students’ perceptions of agriculture and future aspirations, before and after engaging in a four-day agricultural-based program. Graphic elicitation and arts-based projective techniques served as metrics to assess students’ perceptions.Four major themes, with six sub-themes emerged from the data: a) perceptions of agriculture (i.e., previous agriculture); b) strength through unity (i.e., unity; and ripple effect); c) aspirations (i.e., importance of education); d) value of experience (i.e., learning new things; and thankfulness). Overall, the Nicaraguan students indicated the study abroad experience broadened their perspective of agriculture, having a direct impact on their career aspirations.
Keywords: Study abroad; graphic elicitation; agriculture; youth development; 4-S